Exploring EFL Students’ Experiences of Reading-Based Oral Presentations; From Text to Talk - Fitriany Fitriany (BRIGHT VISION, 2025)
This qualitative study explores EFL students’ experiences of reading-based oral presentations in a university speaking course. While integrated-skills instruction is widely recommended, limited research has examined how learners perceive the process of transforming written texts into oral presentations. Using a descriptive–interpretive approach, data were collected through classroom observations, semi-structured interviews, and students’ reflective responses. The data were analyzed thematically to identify recurring patterns in learners’ experiences.The findings reveal four main themes: reading as cognitive support for speaking, increased confidence through content familiarity, gradual negotiation of speaking anxiety, and ownership in meaning construction. The results suggest that reading-based oral presentations function as a scaffolded bridge between comprehension and production, enabling students to organize ideas and articulate interpretations more confidently. Beyond performance outcomes, the activity fostered meaningful engagement and interpretive speaking practices.This study contributes to integrated-skills pedagogy by highlighting learners’ lived experiences in EFL contexts and offers pedagogical insights for designing supportive speaking activities grounded in reading tasks.